Unilateral cross-incompatibility between Camellia oleifera and C. yuhsienensis provides new insights for hybridization in Camellia spp - Gong, Han; Chang, Yihong; Xu, Jinming; Yu, Xinran; Gong, Wenfang (Frontiers in Plant Science, 2023)
Camellia yuhsienensis was used to cross with Camellia oleifera to improve the resistance of oil camellia anthracnose. However, unilateral cross-incompatibility (UCI) between C. oleifera and C. yuhsienensis was found during the breeding process. Five C.oleifera cultivars and four C. uhsienensis materials were tested to confirm the UCI between C. oleifera and C. yuhsienensis. ‘Huashuo’ (HS) and ‘Youza 2’ (YZ2) were used to represent these two species to characterize the UCI, including pollen tube growth, fertilization and fruit development. The results demonstrated that UCI was prevalent between C. oleifera and C. yuhsienensis. The asynchronous flowering period was a pre-pollination barrier that limited mating between these two species under natural conditions. Interspecific pollen tubes were observed through the styles of these two plants, though the growth rates differed considerably. At 96 hours after pollination, the pollen tube of YZ2 barely entered the ovule, but remained at the base of the style and became swollen. However, the HS pollen tube entered the ovule 48 hours after pollination, double fertilization was observed, and the fruit and seeds developed commonly. Relative to compatible combinations, most unfertilized ovules in incompatible combinations failed to grow, turned brown 150 days after pollination, and the fruits were smaller than expected with uneven enlargement. Investigations on both semi-in vivo and in vitro pollen tubes gave us new idea for thought: the HS style has a stronger inhibitory effect on the interspecific pollen tubes, while calcium alleviates the inhibitory of styles but failed to prevent the appearance of abnormal pollen tube morphology. This study provides useful information on interspecific hybridization between C. oleifera and C. yuhsienensis for understanding reproductive isolation mechanisms and breeding programs in genus Camellia.